Research on overcurrent protection curve model and control of solid state power controller - Zhijun Jiang; Junming Zhang; Yufang Lu; Jianjun Zhang (Scientific Reports)
Abstract Partially or fully electrified of advanced equipment has become the main development trend. SSPC (Solid State Power Controller) play a crucial role in ensuring the safe and reliable operation of distribution systems. Inverse time overcurrent protection curve algorithm technology is the key technology to implement SSPC. In this paper, proposes an innovative “heat accumulation” inverse time overcurrent protection algorithm of considering the influence of initial environmental temperature and load line heat dissipation, and the theoretical derivation process of the algorithm is given. The protection time accuracy is improved by about $$10%$$ . The power consumption in multiple scenarios is simulated and analyzed, and the simulation results verify the correctness and accuracy of the algorithm. This provides a new idea for the design of SSPC inverse time overcurrent protection technology.